The Savage way : successfully navigating the waves of business and life - Savage, Frank (Wiley, 2013)
BInspiring lessons on business and life from Frank Savage/b Frank Savage's is an unlikely success story. Raised in segregated Washington, DC, by his mother, a hairdresser and entrepreneur with little formal education, Savage's career has taken him around the world as a globetrotting financier. From his first banking job at Citibank to his current position as Chairman Emeritus of Howard University, iThe Savage Way/i shares the life and business lessons he learned along the way. This memoir relates the many starts and stops, successes and failures in his long career, from his involvement in the collapse of Enron, to his experience investing in Africa, to his days as a competitive yachtsman'always guided by the wisdom of the mother who taught him to transcend all limits./ ulliA powerful memoir of an inspiring business leader/liliSavage is the current Chairman of his alma mater, Howard University, and the CEO of the global financial services company Savage Holdings LLC /li/ul A rare and inspiring story of personal and professional challenge and ultimate triumph, iThe Savage Way/i is a memoir that offers powerful inspiration and wisdom for tomorrow's business leaders.